Using meconium to establish prenatal alcohol exposure in the UK: ethical, legal and social considerations - Arkell, Rachel (Journal of medical ethics, 2023)
An expanding policy framework aimed at monitoring alcohol consumption during pregnancy has emerged. The primary justification is prevention of harm from what is termed ‘prenatal alcohol exposure’ (PAE), by enabling more extensive diagnosis of the disability labelled fetal alcohol spectrum disorder (FASD). Here we focus on proposals to include biomarkers as a PAE ‘screening tool’, specifically those found in meconium (the first newborn excrement), which are discussed as an ‘objective’ measure of PAE. We ask the overarching question, ‘Can routine screening of meconium to establish PAE be ethically or legally justified’, and we answer, ‘No’. To reach this conclusion, we discuss three areas. First, we consider the reasons why meconium screening should not be deemed ‘typical’ within the scope of accepted screening tools. We argue that given the aim and necessary timing of the screen, it cannot achieve what it promises. Second, we outline why patient autonomy and consent are not properly accounted for and cannot be reconciled with the ‘routinisation’ of the proposed ‘screening’. Last, we outline why the benefit of such a screen is not clear, focusing on the significance of trust in healthcare professionals (HCP) for the best interests of the future child and pregnant woman. While recognising the adverse effects of heavy alcohol consumption during pregnancy, we emphasise the case for robust ethical, legal and social considerations and the central need for trust between HCP and patients in maternity care. We conclude the permissibility of meconium screening has not been proven, and it is not justified.